Pengaruh Citra Destinasi Dan Fasilitas Wisata Terhadap Minat Kunjung Wisatawan Pada Objek Wisata Dunia Fantasi (DUFAN) - Salma, Fadia; Manurung, Tarida Marlin Surya (Jurnal Ilmiah Pariwisata Kesatuan, 2023)
This research explanatory it means to study hypothesis variable. In this research use Destination Image and Touris Facilities variable. This research aims to analyze impact to determine the effect simultaneously and parcial Destination Image and Tourist Facilities at Dunia Fantasi. The method is classic assumption test, multiple linear analysis, test T and test F. Data testing is done by using software IBM SPSS Statitics 25. The results of this study indicate that: 1) Destination Image (X1) has a significant effect on Tourist Visit Interests. 2) Tourism Facilities (X2) have a significant effect on Tourist Visit Interests. 3) Destination Image and Tourism Facilities have a simultaneous effect on Tourist Visit Interests. Keyword : Tourism, Destination Image, Tourist Facilities, Tourist Interset.